A multiscale assembly inspection algorithm - Bouman, Charles Addison, author; Tretter, Daniel, author; Maciejewski, Anthony A., author; Khawaja, Khalid W., author; IEEE, publisher (Colorado State University. Libraries, 1996)
An important aspect of robust automated assembly is an accurate and efficient method for the inspection of finished assemblies. This novel algorithm is trained on synthetic images generated using the CAD model of the different components of the assembly. Once trained on synthetic images, the algorithm can detect assembly errors by examining real images of the assembled product.
Keywords: learning systems; visual databases; CAD; assembling; object detection; automatic optical inspection; computer graphics